2021
DOI: 10.1186/s11658-021-00277-6
|View full text |Cite
|
Sign up to set email alerts
|

Burn-induced heterotopic ossification from incidence to therapy: key signaling pathways underlying ectopic bone formation

Abstract: Burn injury is one of the potential causes of heterotopic ossification (HO), which is a rare but debilitating condition. The incidence ranges from 3.5 to 5.6 depending on body area. Burns that cover a larger percentage of the total body surface area (TBSA), require skin graft surgeries, or necessitate pulmonary intensive care are well-researched risk factors for HO. Since burns initiate such complex pathophysiological processes with a variety of molecular signal changes, it is essential to focus on HO in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 85 publications
0
17
0
Order By: Relevance
“… 65 The AOD value showed puerarin increased ALP and BMP2 expression levels during RME, thereby upregulating bone regeneration. Heterotopic ossification (HO) is one of the hot spots of research on post-traumatic complications, 66 , 67 and it has been reported that elevated BMP2 is positively correlated with the occurrence of HO. 68 It is noteworthy that though puerarin upregulates BMP2 level when it is used to stimulate osteogenesis in mid-palatal suture, we presume that HO is less likely to occur in the context of safe, physiological, controlled RME.…”
Section: Discussionmentioning
confidence: 99%
“… 65 The AOD value showed puerarin increased ALP and BMP2 expression levels during RME, thereby upregulating bone regeneration. Heterotopic ossification (HO) is one of the hot spots of research on post-traumatic complications, 66 , 67 and it has been reported that elevated BMP2 is positively correlated with the occurrence of HO. 68 It is noteworthy that though puerarin upregulates BMP2 level when it is used to stimulate osteogenesis in mid-palatal suture, we presume that HO is less likely to occur in the context of safe, physiological, controlled RME.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we found that pain scores were significantly higher in HO patients than non-HO patients both before and after operation. High pain scores may reflect local inflammation around the joint which may affect bone metabolism and lead to the occurrence of HO after surgery [37][38][39]. HO is also a major cause of postoperative pain.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike calcification lesions, HO leads to a complete bone microenvironment within bone tissue cells, microcirculation, and neuroendocrine function. HO patients can experience pain and limited range of motion, which seriously impairs their activity of daily living [3]. Pathogenesis is not yet clear, although some studies found that it's multifactorial and the major factor identified is trauma.…”
Section: Discussionmentioning
confidence: 99%